More on the penetration of spherical-nosed rigid projectiles into metallic targets. Issue 1 (March 2023) - Vayig, Yaniv; Rosenberg, Zvi; Ornai, David
This work deals with several issues related to the deep penetration of spherically nosed rigid projectiles impacting metallic targets at normal incidence. The most important issues in these processes are the constant resisting stress acting on the projectile beyond the initial entrance phase, the extent of the entrance phase, and the onset of cavitation at impact velocities higher than a certain threshold velocity. In this work, we derive a new relation for the target's resisting stress in terms of its bulk and shear moduli and we also use a simplified analysis to account for the effect of the entrance phase on the depth of penetration for spherically nosed rigid projectiles. In addition, we highlight the role of cavitation in this process through numerical simulations for targets having very different densities.